Optimizing Project Efficiency Through Implementing Knowledge Management at Gunanusa Utama Fabricators (Oil & Gas) - Hilda Yolanda*; Dedy Sushandoyo (Universitas Syiah Kuala, 2023)
Gunanusa Utama Fabricator, an Engineering, Procurement, Construction, and Installation (EPCI) company in Jakarta, Indonesia, is confronted with challenges in project efficiency due to a high rejection rate in welders' production. This study aims to develop a knowledge management framework tailored to daily contract workers at Gunanusa, with a particular focus on welders. The objective is to establish a connection between worker engagement, development activities, and project efficiency optimization. Adopting a qualitative approach, the research incorporates stakeholder interviews and examination of project-related documentation. The SECI model (Socialization, Externalization, Combination, and Internalization) serves as the foundational model for knowledge management activities. The findings underscore the significance of knowledge management practices in fostering collaboration, communication, and continuous learning within the organization. Recommendations are provided to enhance Gunanusa's knowledge management system, including the development of internalization activities and the utilization of technology for knowledge storage and retrieval. An implementation plan is outlined to guide Gunanusa in adopting the knowledge management framework and cultivating a culture of knowledge sharing and continuous learning. This study contributes to the existing literature by emphasizing the importance of knowledge management practices in optimizing project efficiency for daily contract workers, particularly welders, at Gunanusa Utama Fabricators. The research offers practical implications for organizations aiming to enhance project outcomes through effective knowledge management strategies.